Evaluation of Physical, Health Promoting Properties and Storage Stability of Ready-to-Drink Mixed Tea from Riceberry Rice and Mulberry Leaf - Ngamdee, Paradorn (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2022)
This study aimed to present the development of healthy ready-to-drink (RTD) tea from Riceberry rice tea infusion (RBTI) and mulberry leaf green tea infusion (MGTI). The color of RBTI was red with a positive a* value (8.1) due to the anthocyanins which were found only in RBTI. The MGTI color was pale green with a positive b* value (12.9). Four formulas of the RTD mixed teas were prepared by varying the ratio of RBTI:MGTI at 50:50, 60:40, 70:30, and 80:20 v/v. The color of the RTD mixed teas changed toward red pertaining to the content of RBTI. As the ratio of RBTI increased, the anthocyanin content in the RTD mixed teas increased. As a result, the 80:20 formula had a higher anthocyanin content (14.4 mg/L). However, total phenolic content (14.3 - 15.6 mg GAE/L) and DPPH antioxidant activity (49.2 - 52.9 %) of all four formulas changed insignificantly. The sensory test results indicated that 70:30 and 80:20 formulas received high liking scores on bitterness, overall flavor, and overall liking attributes. The 80:20 formula was selected as the most preferable formula in this study because of its high anthocyanin content. The evaluation of the storage stability of the 80:20 formula revealed that the color, total soluble solid content, anthocyanin, phenolic content, and DPPH antioxidant activity of the tea changed significantly on day 15. These results indicated that the RTD mixed tea from Riceberry rice and mulberry leaf was a healthy tea with consumer acceptance and adequate storage stability.